2001
DOI: 10.1128/aac.45.1.280-287.2001
|View full text |Cite
|
Sign up to set email alerts
|

A Spectrum of Changes Occurs in Peptidoglycan Composition of Glycopeptide-Intermediate Clinical Staphylococcus aureus Isolates

Abstract: The mechanism of glycopeptide resistance in Staphylococcus aureus is not known with certainty. Because the target of vancomycin is the D-Ala-D-Ala terminus of the stem peptide of the peptidoglycan precursor, by subjecting muropeptides to reversed-phase high-performance liquid chromatography, we investigated peptidoglycan obtained from glycopeptide-intermediate S. aureus (GISA) isolates for changes in composition and evaluated whether any peptidoglycan structural change was a consistent feature of clinical GISA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
79
1
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 21 publications
3
79
1
4
Order By: Relevance
“…En ambas cepas la expresión de PBP4, una carboxipeptidasa y transpeptidasa secundaria que se requiere para el (43). Aunque las hipótesis mencionadas explican parcialmente el mecanismo de resistencia a vancomicina, se han aislado unas pocas cepas VISA que no tienen estas alteraciones en la pared celular, lo que hace pensar que la resistencia debe obedecer a mecanismos alternativos aún sin estudiar (44).…”
Section: Resistencia Intermedia a Vancomicina: Cepas Visaunclassified
“…En ambas cepas la expresión de PBP4, una carboxipeptidasa y transpeptidasa secundaria que se requiere para el (43). Aunque las hipótesis mencionadas explican parcialmente el mecanismo de resistencia a vancomicina, se han aislado unas pocas cepas VISA que no tienen estas alteraciones en la pared celular, lo que hace pensar que la resistencia debe obedecer a mecanismos alternativos aún sin estudiar (44).…”
Section: Resistencia Intermedia a Vancomicina: Cepas Visaunclassified
“…Каприн, Е.В. Филоненко Исследование фотосенсибилизатора для антибактериальной фотодинамической терапии на основе циклодекстриновой композиции метилового эфира 13 3 …”
unclassified
“…Pharmacokinetics and biodistribution of PS were studies in vivo in organs and tissues of intact mice and septic wounds infected with P. аeruginosa or S. aureus. The preliminary studies have shown high efficiency of antimicrobial photodynamic therapy of septic wounds with cyclodextrin dispersion of 13 3 -N-(N-methylnicotinyl)-bacteriopurpurinimide methyl ester. Results of study of absorption and spectral and fluorescence properties of its drug formulation depending on its composition allowed to recommend the use of weight ratio 13 3 -N-(N-methylnicotinyl)-bacteriopurpurinimide methyl ester : cyclodextrin about 1:200 and addition of 0,1% Tween 80 to reduce aggregation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations